Reduction of Mn(III) in Pyrophosphate Medium by Diketones: Kinetics and Mechanism - HIRAN, B.L.; MALKANI, R.K.; DANGARH, B.K.; AMB, B.K. (Asian Journal of Chemistry, 2010)
Oxidation of acetylacetone and benzoyl acetone by Mn(III) pyrophosphate has been investigated. Benzoyl acetone undergoes C-C cleavage while acetylacetone undergoes C-H cleavage. This has been confirmed by product study and supports the proposal that large negative entropy of activation study and supports the proposal that large negative entropy of activation is associated with C-H cleavage and large positive value is associated with C-C cleavage. The energy of activation observed for benzoyl acetone is 97.8 kJ mol–1 while for acetyl acetone 35.7 kJ mol–1. Relevant mechanisms have been suggested which are consistent with the observed rate laws. In both these oxidations free radical intervention and Michaelis-Menten type of kinetics is observed. In similar conditions benzoyl acetone reacts faster than acetyl acetone. The reactions obey the rate law (K is complex formation constant between Mn (III) pyrophosphate and substrate.)